Industrial violence and the legal origins of child labor / James D. Schmidt. - Schmidt, James D. (Cambridge historical studies in American law and society., 2010)
Industrial Violence and the Legal Origins of Child Labor challenges existing understandings of child labor by tracing how law altered the meanings of work for young people in the United States between the Revolution and the Great Depression. Rather than locating these shifts in statutory reform or economic development, it finds the origin in litigations that occurred in the wake of industrial accidents incurred by young workers. Drawing on archival case records from the Appalachian South between the 1880s and the 1920s, the book argues that young workers and their families envisioned an industrial childhood that rested on negotiating safe workplaces, a vision at odds with child labor reform. Local court battles over industrial violence confronted working people with a legal language of childhood incapacity and slowly moved them to accept the lexicon of child labor. In this way, the law fashioned the broad social relations of modern industrial childhood.